Coronavirus disease (COVID-19) and the need to maintain regular physical activity - Amekran, Y.; El Hangouche, A. J. (The Journal of Sports Medicine and Physical Fitness, 2021)
LETTERS TO THE EDITOR The novel Coronavirus disease (COVID-19) caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-COV-2) was first reported in December 2019 in China, and has rapidly spread worldwide. Due to a sharp increase in the number of confirmed cases of infection and death, administrative Orders were issued to contain the virus spread and they shut down all facilities, including national and international travel, recreation facilities, parks and playgrounds, except the essential ones. Although this strategy has been reported to be efficacy for containing the COVID-19 outbreak, it has forced populations to radically change their daily habits leading to undesirable effects, especially on mental health and physical activity practice. Some individuals may have sufficient autonomous regulation of physical activity to exert altemate activities like online fitness classes, but others may reduce or stop their physical activity due to the lack of social support available or concems for contracting the virus in an outdoor environment, leading to a decrease in physical activity. In this context, negative changes in physical activity of individuals during the period of COVID-19 were assessed. Strong reduction of vigorous activity and walking was reported. These data reflect the major difficulties to walk and perform an intense exercise at home. In addition, it has been also showed that during the pandemic, the physical activity levels significantly decreased in all age groups. Moreover, in an Australian survey, more than 48% of participants reported a negative change (reduction) in physical activity since the onset of the COVID-19 pandemic.